2004
DOI: 10.1007/s10334-004-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

A new pulse sequence to visualize slow flow

Abstract: The purpose of this paper is to present a new pulse sequence for visualizing slow flow. The new sequence consists of an initial Stejskal-Tanner flow sensitization part followed by a DEFT pulse and a spoiler gradient. A single-shot TSE readout train is then applied to sample the NMR signal. The sequence was initially tested using a simple flow phantom. To verify potential clinical use, both flow-sensitive MRCP and cerebrospinal fluid (CSF) images were produced. The phantom study proved the sequence sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Additionally, this technique is not physiologic because it requires the injection of secretin. Other reports have suggested that pancreatic juice fl ow could be detected by using a single-shot turbo spin-echo sequence based on a diffusion-weighted MR imaging technique (18)(19)(20). In this approach, the stationary pancreatic fl uid appears bright, while the moving pancreatic fl uid loses signal intensity as the b value used increases and appears as a fl ow void.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, this technique is not physiologic because it requires the injection of secretin. Other reports have suggested that pancreatic juice fl ow could be detected by using a single-shot turbo spin-echo sequence based on a diffusion-weighted MR imaging technique (18)(19)(20). In this approach, the stationary pancreatic fl uid appears bright, while the moving pancreatic fl uid loses signal intensity as the b value used increases and appears as a fl ow void.…”
Section: Discussionmentioning
confidence: 97%
“…The pulse sequence used in this study to visualize changes in slow flow in the PD has been presented previously (5). Initial tests in an experimental study showed that semi-quantitative evaluation of flow was possible (6).…”
Section: Discussionmentioning
confidence: 99%
“…The study shows that changes in the slow flow of the PD can be detected, but the method is very sensitive to bowel movement artifacts, and thereby probably any movement during scanning, including any physiological flow within the PD. Signal fluctuation, which occurs earlier with increasing b factor, is also suspected to effect the visibility score (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations